Comparison of preoperative myometrial invasion on MRI with intraoperative frozen section in predicting adverse prognostic factors and survival in endometrioid endometrial cancer (Annals of Medical Research, 2019)
Aim: There are no studies that have evaluated the accuracy of the finding of myometrial invasion in each modality in predicting adverse prognostic factors and survival. We compared the association of myometrial invasion on MRI and frozen section with presence of adverse prognostic factors and decreased disease-specific survival (DSS) in endometrioid endometrial cance. Material and Methods: A total of 149 patients diagnosed and treated surgically for endometrioid endometrial cancer at a single institution between 2010 and 2017 were included in the study. Accuracies of radiological myometrial invasion and frozen section myometrial invasion in predicting the histopathological myometrial invasion, other adverse prognostic factors and DSS were compared.Results: Frozen section had an accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 89.2%, 100.0%, 84.7%, 72.8% and 100.0%, respectively in diagnosing histopathological deep (≥50%) myometrial invasion with a kappa value of 0.876 (p